Specifics of Educational Activity Anti-motivation in Future Teachers Subject to the Training Period - Akpayeva, Assel Bakirovna; Ivanova, Natalia Valentinovna; Luchina, Tatiana Ivanovna; Minaeva, Elena Viktorovna; Zhestkova, Elena Alexandrovna (International Review of Management and Marketing, 2016)
The study objective was the analysis of specifics of educational activity antimotivation in students of pedagogical universities – future teachers in various training periods. 282 students (years 2-5) of Russian and Kazakh pedagogical universities took part in the study. In order to achieve the study objective we used a questionnaire on antimotivation in educational activity developed by N.V.Ivanova, E.V.Minayeva for students of pedagogical universities. According to the results of the study, psychodidactic antimotivation determinant of educational activity has the highest statistically significant impact among the students of various pedagogical universities. It has been proved that there is a correlation dependence between the singled out environmental antimotivation determinants of educational activity in students of various pedagogical universities. No statistically significant differences between mean values of antimotivation determinants of educational activity in pedagogical students at various training stages have been discovered. This attests stability in determination of educational activity antimotivation in respondents from pedagogical universities for the whole training period. Antimotive development quantitative levels have been singled out having different environmental determinants, dynamic specifics of their development in students subject to their training period have been established. The results obtained may be used to optimize educational activity of pedagogical students. Keywords: educational activity antimotivation, student, pedagogical university JEL Classifications: I21, I23